Effects of air-entraining agent and polypropylene fiber on the mechanical properties, autogenous shrinkage, and fracture properties of fully recycled aggregate concrete - Ding, Dong; Zhang, Lijuan; Zhao, Jun; Li, Changbin; Wang, Zhi (Frontiers in Materials, 2022)
The effect of air-entraining agent (AEA) and polypropylene fiber (PPF) on the autogenous shrinkage and fracture properties of fully recycled aggregate concrete (FRAC) are studied to obtain FRAC with low density, low autogenous shrinkage and good fracture properties. There are 6 groups of FRAC with different AEA contents (0,5%,10%) and different PPF contents (0,1.2kg/m3) were prepared for test. The results illustrated that adding AEA can slightly reduce the density, but it has an adverse effect on the strength and fracture properties of FRAC. Adding PPFs can reduce the adverse effect of AEA on compressive strength and splitting tensile strength, but it will increase the adverse effect on fracture properties. Furthermore, at the content of AEA is 0, the addition of PPFs will significantly reduce the compressive strength and splitting tensile strength, whereas the flexural strength and fracture properties are increased. Adding AEA can improve the adverse effect of PPF on compressive and splitting tensile strength, but the flexural strength and fracture properties will transform from increase to decrease. The addition of 10% AEA can greatly reduce the autogenous shrinkage, and 5% AEA can reduce the autogenous shrinkage of early age. Incorporation of PPFs can further reduce the autogenous shrinkage. The study mainly studies the effect of AEA and PPF on the autogenous shrinkage of FRAC, which provides some new ideas for making high-performance FRAC. At the same time, the cooperative effect of AEA and PPF on the properties of FRAC is studied.